Mitigating gaseous nitrogen emissions in cotton fields through green manure and reduced nitrogen fertilization - Ru Ma; Zhenggui Zhang; Jian Wang; Yingchun Han; Ke Li; Mengyao Hou; Mengyao Hou; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Yahui Jiao; et al. (Frontiers in Microbiology)
Integrating green manure with reduced nitrogen (N) fertilization is a promising strategy to mitigate N emissions in intensive cotton cultivation, however, the underlying mechanisms remain poorly understood. This study investigated the effects of three green manure incorporation patterns—no green manure (NG), Orychophragmus violaceus (OVG), and Vicia villosa (VVG)—combined with four N reduction levels (100, 50, 25%, and conventional) on gaseous N emissions (NH3 and N2O), soil physicochemical properties, and bacterial community characteristics using a cotton field experiment in the Yellow River Basin. Results showed that OVG incorporation with 25% N reduction (N2 treatment) significantly reduced total gaseous N emissions by 36.07% on average during the cotton growth period, reducing NH3 and N2O emissions by 13.31–54.11% and 32.25–68.77%, respectively, compared with N2 application without OVG. OVG application also increased the relative abundance of Proteobacteria (28.10%), enhanced heterogeneous selection in bacterial community assembly (200%), and increased the complexity of co-occurrence networks, compared with NG. Compared with conventional N fertilization (N3 treatment), ≥50% N reduction significantly lowered NH3 (>25.51%) and N2O (>32.76%) emissions, reduced the relative abundance of Acidobacteria (−20.23%), simplified co-occurrence networks, and increased homogeneous selection in bacterial assembly (50.00%). Integrating green manure with 25% N reduction substantially reduced gaseous N emissions, which was associated with the enhanced microbial biomass carbon (MBC) and facilitated recruitment of key bacterial taxa (e.g., Sphingosinicella, Azohydromonas, Phototrophicus) within the microbial co-occurrence network. These findings provide insight into how green manure application coupled with N reduction can mitigate gaseous N losses and reshape soil microbial ecology, offering a theoretical basis for sustainable nutrient management during cotton production.